2015
DOI: 10.1039/c5cp03880d
|View full text |Cite
|
Sign up to set email alerts
|

Building solids inside nano-space: from confined amorphous through confined solvate to confined ‘metastable’ polymorph

Abstract: The nanocrystallisation of complex molecules inside mesoporous hosts and control over the resulting structure is a significant challenge. To date the largest organic molecule crystallised inside the nano-pores is a known pharmaceutical intermediate - ROY (259.3 g mol(-1)). In this work we demonstrate smart manipulation of the phase of a larger confined pharmaceutical - indomethacin (IMC, 357.8 g mol(-1)), a substance with known conformational flexibility and complex polymorphic behaviour. We show the detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…62 It is known that nanoconfined/surface molecules demonstrate increased mobility that may lead to loss 23 of CP signal. 22,[63][64][65][66] Furthermore, the decreased signal intensity in the CP/MAS experiment can be related partially to the paramagnetic impurities present in the naturally sourced clay, that is, 2.9 wt% of the Fe(III) ions. 67 The substantial decrease in the longitudinal (T1) relaxation times due to contribution from electron-nuclear spin relaxation mechanism led to an overall decrease of the signal intensity.…”
Section: The Decrease Of the Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…62 It is known that nanoconfined/surface molecules demonstrate increased mobility that may lead to loss 23 of CP signal. 22,[63][64][65][66] Furthermore, the decreased signal intensity in the CP/MAS experiment can be related partially to the paramagnetic impurities present in the naturally sourced clay, that is, 2.9 wt% of the Fe(III) ions. 67 The substantial decrease in the longitudinal (T1) relaxation times due to contribution from electron-nuclear spin relaxation mechanism led to an overall decrease of the signal intensity.…”
Section: The Decrease Of the Cpmentioning
confidence: 99%
“…Recently it has been demonstrated that increased stabilization of amorphous drug and excipients can be obtained by mixing these with inert clay or silicate particles, or by nanoconfinement within mesoporous silica. [22][23][24][25][26][27] The advanced studies of structure and dynamics in such materials at different lengths scales, that is, from molecular level to meso-and microstructure are needed to provide a more detailed insight into the origins of control of physical stability and compaction properties.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Furthermore,the engineering of nanocrystals confined within nanosized chambers of controlled pore glasses yielded new crystalline structures,s tabilized metastable polymorphs,o r helped formulating amorphous drug-delivery systems. [3][4][5] Although the number of studies aimed at new applications of porous silica materials is rising, there is aconsiderable lack of molecular-level understanding of the phenomena that govern self-assembly in such systems.For example,ibuprofen, benzoic acid, and lauric acid confined within MCM-41 silica (pore diameter ca. 3-4 nm) have been found to be in ahighly mobile state,a sl iquid-like behavior was observed by solidstate NMR spectroscopy.…”
mentioning
confidence: 99%
“…The metastable α‐polymorph of indomethacin was also found to crystallize selectively on the layered cellulose nanocrystals generated by dip coating (Lu et al, ). A recently discovered form V of indomethacin was found to stabilize in nanoconfinement of the controlled porosity silica (Nartowski, Tedder, Braun, Fábián, & Khimyak, ). Metastable polymorphs of olanzapine (Warzecha et al, ), tolbutamide (Zhang et al, ) and mefenamic acid (Case et al, ) were also successfully crystallized using different heterosurfaces.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%